2022
DOI: 10.1136/bcr-2022-252518
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune glial fibrillar acidic protein astrocytopathy mimicking tuberculous meningitis

Abstract: Autoimmune glial fibrillar acidic protein (GFAP) astrocytopathy typically presents as acute or subacute meningoencephalitis with or without myelitis. We describe a case of autoimmune GFAP astrocytopathy that mimicked tuberculous meningitis. A man in his 70s was referred to our hospital with lethargy persistent for 2 months, appetite loss for 1 month and fever with headache for 10 days. The cerebrospinal fluid test revealed lymphocytic pleocytosis with elevated adenosine deaminase (ADA). Laboratory investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Internal jugular thrombophlebitis is often unilateral, but bilateral involvement has also been described16 and pulmonary complications are attributed to septic emboli. Lemierre syndrome is most commonly caused by F. necrophorum , an obligate anaerobic gram-negative bacillus that is part of the normal flora of oral cavity, gastrointestinal and female genital tract.…”
Section: Discussionmentioning
confidence: 99%
“…Internal jugular thrombophlebitis is often unilateral, but bilateral involvement has also been described16 and pulmonary complications are attributed to septic emboli. Lemierre syndrome is most commonly caused by F. necrophorum , an obligate anaerobic gram-negative bacillus that is part of the normal flora of oral cavity, gastrointestinal and female genital tract.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated CSF lymphocytes, protein is more common in TBM; autoimmune disease is uncommon. Studies have revealed that the cerebrospinal fluid of A-GFAP-A patients is predominantly characterized by inflammatory changes and that CSF lymphocytes and proteins can be increased, with some patients exhibiting CSF protein > 1.0 g/L [2,[4][5][6][8][9][10]. A CSF protein threshold of > 1.0 g/L (100 mg/dL) differentiated between cases of TBM, bacterial meningitis [17], and viral meningitis [18].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical symptoms include fever, headache, brain and meningeal abnormalities, imaging and cerebrospinal fluid changes, lack of specificity, and susceptibility to misdiagnosis. Especially when the cerebrospinal fluid depicts tuberculous lesions, it is easily confused with tuberculous meningitis (TBM) [3][4][5][6][7][8][9]. This study retrospectively examined the clinical features of A-GFAP-A in patients with tuberculous meningitis to improve understanding and diagnostic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…W piśmiennictwie coraz częściej opisywane są zakażenia zlokalizowane poza jamą ustną. Gatunek ten wyizolowano z próbek pobranych w przebiegu zakażenia okołoprotezowego stawów (12,18), zakażeń ran, ropni (13,19), ciężkiego ropniaka z zespołem ostrej niewydolności oddechowej (20), bakteriemii (21)(22)(23) i zapalenia opon mózgowo-rdzeniowych (24,25).…”
Section: Methodsunclassified
“…More reports of S. exigua extra-oral infections are being published. This species has been isolated from periprosthetic joint infections (12,18), human wound infections, abscesses (3,19), severe empyema with acute respiratory distress syndrome (20), bacteremia (21)(22)(23), and meningitis (24,25).…”
Section: Wstępmentioning
confidence: 99%